PENGARUH DOSIS KOMPOS KULIT GELONDONG KOPI DAN PUPUK MAJEMUK TERHADAP PERTUMBUHAN DAN HASIL TANAMAN BAWANG MERAH (Allium ascalonicum L.) - S.P., M.Agr, Whin Themas Mico Saputra; Mulyono, Mulyono; Fadli, Rahmad (Cangkok, 2021)
This research is generally to determine the effect of giving a dose of coffee logs skin compost and compound fertilizer as well as the interaction on the growth and yield of shallot (Allium ascalonicum, L.) which was carried out in Pante Raya Village with an altitude of 1200 meters above sea level with Andosol soil type with Soil pH 6.8. The dose treatment of coffee bark compost can increase the growth and yield of shallots as shown in plant height at the age of 15, 30 and 45 days after planting, the number of leaves at the age of 30 and 45 days after planting, the number of tillers at the age of 30, 45 and 60. days after planting, the weight of wet safes per clump and per plot at 90 days after planting and the best dose was 1 kg/polybag (D2). The dose treatment of NPK Basf compound fertilizer increased the growth and yield of shallots as indicated by plant height at 15, 30 and 45 days after planting, number of leaves at 30 and 45 days after planting, number of tillers at 30, 45 and 60 days. days after planting, the weight of wet safes per clump and per plot at 90 days after planting and the best dose was 6 grams/polybag (M2). There was no interaction between the dose of coffee bark compost and the dose of NPK Basf compound fertilizer on the growth and yield of shallots.